IS THERE A PERSPECTIVE FOR A NEW PARADIGM IN ECONOMICS? - Čičinskas, Jonas (Ekonomika, 2011)
It was long before the current economic crisis has triggered a new wave of criticism towards the very foundation of capitalism – the market system, that a discontent with deepening divergence between the pure economic theory and the agenda the economic policy has been dealing with was proliferating. Aattempts of refining the paradigm or its replacement with a new one were undertaken. The objective of the study was to review the main failures and incapacities the neoclassical economic theory is experiencing and to identify the possible trait components most appealing for modification and refining. The vast and unstoppable waste of resources (labour, but not only) by the modern market system, negation of the permanent and necessary presence of state in the economy as an integral economic agent, distortion of goals of economic activity by limiting them by the quantitative maximization of produce – these are the main traits of failure of the current theoretical model in satisfying requirements for a better understanding of modern economy. They are also the arguments for the criticism of its paradigm.The analytical method was used to penetrate the current discussion and other data in order to disclose the paradigmatic content of the theoretical perception of modern economy. The results of the whole study are new in terms of the fulfilled attempt to systemize criticisms of market system failures and to point out the possible components of its paradigm, which pretend to be modified. The conclusion is drawn that the paradigm of mainstream economics has no alternatives, but the growing mismatch between the realities of modern economic life and presumptions and the conclusions of the neoclassical model of economy asks for its revision or modification.